2013
DOI: 10.1177/1750698013482868
|View full text |Cite
|
Sign up to set email alerts
|

Memory and history in twenty-first century Australia: A survey of the field

Abstract: This essay surveys the fields of oral history and memory studies in Australia since the publication of the landmark volume Memory and History in Twentieth-Century Australia in 1994. It argues that the practice of oral history has been central to memory studies in Australia, and explores key texts relating to the memory and commemoration of war, colonialism, Indigenous histories, trauma and witnessing in Australian society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Cultural/collective memory is the act of recalling events that are related with objects, places and encountered by people in a social framework or between groups that experience these events [16]. Collective memory is reckoned to be a repository of culture, and sometimes this view leads to the term 'cultural memory' being used interchangeably [17]. Cultural memory (or collective memory) was parented for the first time into the literature by Maurice Halbwachs in his books The Social Frameworks of Memory (1992 and 1925) and On Collective Memory (1980 and 1950).…”
Section: Cultural Memorymentioning
confidence: 99%
“…Cultural/collective memory is the act of recalling events that are related with objects, places and encountered by people in a social framework or between groups that experience these events [16]. Collective memory is reckoned to be a repository of culture, and sometimes this view leads to the term 'cultural memory' being used interchangeably [17]. Cultural memory (or collective memory) was parented for the first time into the literature by Maurice Halbwachs in his books The Social Frameworks of Memory (1992 and 1925) and On Collective Memory (1980 and 1950).…”
Section: Cultural Memorymentioning
confidence: 99%
“…Academics such as Goodall (2008), Attwood (2001), Darian-Smith and Hamilton (2013) have observed that a collective history and memory play a large part in determining Australian identity. In the past, politicians such as John Howard have sought to "instrumentalise Australian history for political ends" (Bonnell and Crotty 2008, p. 151).…”
Section: Australian Collective Historymentioning
confidence: 99%
“…However, understandings of ‘Australian heritage’ have been troubled by the fact – of increasing political salience since the 1970s – that Australia is a settler colonial society (Darian-Smith and Hamilton, 2013). Many Australians now ask, ‘Are there not two stories of service and sacrifice to be distinguished – the Indigenous and the non-Indigenous?’ With strong support from the Australian government, custodians of Anzac memory now readily acknowledge that Indigenous Australians were among those enlisted or conscripted to military service: their contributions have been honoured, and government-funded teaching materials have reinforced the idea that Indigenous Australians, too, were patriots who served unselfishly.…”
Section: Military Heritage and Australian Identitymentioning
confidence: 99%
“…Although difficult heritage ‘threatens to trouble collective identities and open up social differences’ (Macdonald, 2009: 4), it has nonetheless been given material form in museum displays, monuments and state apologies because the strenuous embracing of ‘difficult heritage’ signals to others a nation’s ‘moral cleanliness and honesty’ (Macdonald, 2015: 19). In Australia, public remembrance of the infliction of trauma and violence on Indigenous Australians is contested, but many Australians have committed to tracing the legacies of colonialism (Darian-Smith and Hamilton, 2013), including labelling as ‘Frontier War’ the violent clashes between colonists and Indigenous Australians (Clark, 2016).…”
Section: Military Heritage and Australian Identitymentioning
confidence: 99%